UPAYA PENANGANAN SENGKETA KEPEMILIKAN SERTIFIKAT GANDA OLEH BPN DI KABUPATEN GRESIK - Sucipto, Rizky Awaludin Bagus; Prawesti, Wahyu (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Duplicate land certificates pose a significant challenge to Indonesia’s agrarian system, as they generate legal uncertainty and undermine land ownership rights. This issue reflects weaknesses in land administration and the lack of data integration within the National Land Agency (BPN). This study investigates the dispute resolution mechanisms applied by the Gresik Regency Land Office and evaluates the legal protection afforded to legitimate certificate holders. Employing an empirical legal method with a descriptive-qualitative approach, data were collected through interviews, observations, and documentation. The findings reveal that although BPN Gresik implements administrative procedures in line with Government Regulation No. 24 of 1997 on Land Registration, shortcomings persist, particularly in the verification process and information system integration. Moreover, legal protection for holders of original certificates remains suboptimal due to limited restitution mechanisms and inconsistent regulatory enforcement. The study highlights the urgency of digital-based land administration reform, along with the need for greater transparency, accountability, and the development of fair and efficient non-litigation dispute resolution mechanisms